2008
DOI: 10.1089/cap.2008.012
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Utilization at a Group-Home Residential Facility for Children and Adolescents

Abstract: There was a high rate of psychotropic medication utilization among this population, though utilization rates dropped significantly over the course of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…TFM homes implement a well-specified model that utilizes proactive behavior approaches focused on promoting youth strengths, highly trained and supervised staff, ongoing professional consultation, and a focus on family-style living (U.S. Department of Health and Human Services, 1999;Wolf et al, 1995;Wolf et al, 1976). Many of the core TFM elements have been linked to positive youth outcomes (e.g., Friman et al, 1996;Gilman & Handwerk, 2001;Handwerk, Smith, Thompson, Spellman, & Daly, 2008;Handwerk, Turk, Hoff, Lucas, & Friman, 2006;Jones & Timbers, 2003;Larzelere, Daly, Davis, Chmelka, & Handwerk, 2004;Lee, Chmelka, & Thompson, 2010;Lee & Thompson, 2009;McNeal, Field, Handwerk, Roberts, & Friman, 2006). Much of this evidence, however, is either very dated or based on selected settings (Fixsen & Blasé, 2002;Kirigin, Braukmann, Atwater, & Wolf, 1982;Lazelere, Smith, & Daly, 1997;Thompson et al, 1996).…”
Section: Journal Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…TFM homes implement a well-specified model that utilizes proactive behavior approaches focused on promoting youth strengths, highly trained and supervised staff, ongoing professional consultation, and a focus on family-style living (U.S. Department of Health and Human Services, 1999;Wolf et al, 1995;Wolf et al, 1976). Many of the core TFM elements have been linked to positive youth outcomes (e.g., Friman et al, 1996;Gilman & Handwerk, 2001;Handwerk, Smith, Thompson, Spellman, & Daly, 2008;Handwerk, Turk, Hoff, Lucas, & Friman, 2006;Jones & Timbers, 2003;Larzelere, Daly, Davis, Chmelka, & Handwerk, 2004;Lee, Chmelka, & Thompson, 2010;Lee & Thompson, 2009;McNeal, Field, Handwerk, Roberts, & Friman, 2006). Much of this evidence, however, is either very dated or based on selected settings (Fixsen & Blasé, 2002;Kirigin, Braukmann, Atwater, & Wolf, 1982;Lazelere, Smith, & Daly, 1997;Thompson et al, 1996).…”
Section: Journal Ofmentioning
confidence: 99%
“…Pre-post findings about change across time while youth reside in TFM homes have been mostly positive (Gilman & Handwerk, 2001; Handwerk et al, 2008; Handwerk et al, 2006; Larzelere et al, 2004; Lee et al, 2010; Lee & Thompson, 2009; McNeal et al, 2006). Outcomes include higher youth-reported hope for the future (McNeal et al, 2006); increased self-reported life satisfaction related to view of self, school, and friends (Gilman & Handwerk, 2001); and significantly fewer youth meeting criteria for psychiatric disorders (Handwerk et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we conducted our first study related to this issue using archival data to track medication use at admission to the Family Home Program, during care, and at discharge. We found that 40% of youth were admitted on psychotropic medications compared with 26% at discharge (Handwerk, Smith, Thompson, Spellman, & Daly, 2008). We also found that youth departing on medication were more likely to be male, younger, and rated as doing more poorly in the program.…”
Section: Dominant Lines Of Research Related To Residential Carementioning
confidence: 99%
“…It has also been reported that, on average, these youth experience clinical levels of both internalizing and externalizing behavior problems and between 55 and 60% engage in aggressive behavior (Breland-Noble et al 2005;CWLA 2005;Duppong Hurley et al 2009;Pottick et al 2005). As a result, it is not surprising that many of the youth who enter residential treatment have active prescriptions for psychiatric medications (Connor and McLaughlin 2005;Handwerk et al 2008).…”
Section: Introductionmentioning
confidence: 99%